If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 69 = 8c + -3 Reorder the terms: 69 = -3 + 8c Solving 69 = -3 + 8c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8c' to each side of the equation. 69 + -8c = -3 + 8c + -8c Combine like terms: 8c + -8c = 0 69 + -8c = -3 + 0 69 + -8c = -3 Add '-69' to each side of the equation. 69 + -69 + -8c = -3 + -69 Combine like terms: 69 + -69 = 0 0 + -8c = -3 + -69 -8c = -3 + -69 Combine like terms: -3 + -69 = -72 -8c = -72 Divide each side by '-8'. c = 9 Simplifying c = 9
| 6e-1=11 | | -3t^2-14t+4=0 | | x^2*14x+40=0 | | 8x^2+25x-200=0 | | 20x=192 | | 4x^2+25-200=0 | | ((2x-1)/(x+2))+((x+2)/(2x-1))=(10/3) | | 8x^2-7x=4x-14x^2 | | 0.06/0.02 | | (3x+8)=(9x-4) | | 6x+105=14x-7 | | 119-4x=41x+19 | | 8y+1000/Y=0 | | 2y^2-50y+308=0 | | 135+x=90 | | 8y+1000/Y | | 135+x=180 | | 4/5-2/4 | | -45=-6f(-3f-4) | | -2x+5y+7=0 | | x+40+5x+14+90=180 | | 6/7-2/5 | | 7x+2=13x-3 | | y^2+25y+154=0 | | 4/6-2/9 | | (x-4)(x-4)-25=0 | | 3*2-(2-5)=9 | | 8.3-0.6x=11.3 | | 5x+130=13x-6 | | 11.3-0.6x=11.3 | | 6X+5-8X+15= | | 7x^2-49x+17=0 |